Gene expression values of pattern-recognition receptors in porcine leukocytes and their response to Salmonella enterica serovar Typhimurium infection - Osvaldova, Alena; Stepanova, Hana; Faldyna, Martin; Matiasovic, Jan (Research in veterinary science, 2017)
Pattern-recognition receptors (PRRs) recognize pathogen-associated molecular patterns and play an important role in triggering innate immune responses. PRRs distribution and function is well documented in mice and humans, but studies in pigs are scarce. Salmonella enterica serovar Typhimurium is common pathogen found in pigs and was used as a model for interaction with PRRs. This study investigated expression of PRRs in porcine leukocyte subpopulations at the mRNA level. Eight subpopulations of leukocytes comprising NK cells, Th, Tc, double positive T cells and γδ T cells, B cells, monocytes and neutrophils were sorted, and the expression of 12 PRRs was measured, including selected Toll-like receptors and their co-receptors, NOD-like receptor NOD2, RP-105, CD14, and dectin. The highest expression rates of most PRRs were observed in monocytes and neutrophils. The B cells expressed high levels of TLR1, TLR6, TLR9, TLR10, and RP-105. Only monocytes and γδ T cells were found to respond to Salmonella enterica serovar Typhimurium infection by intensification of PRRs expression. In Th and B cells, PRRs mRNA down-regulation was detected after infection.
Keywords: T-lymfocyty; RNA, Messenger; Toll-like receptors; zvířata; toll-like receptory; salmonelová infekce u zvířat; regulace genové exprese; Neutrophils; Gene Expression Regulation; messenger RNA; Leukocytes; Pig; leukocyty; přirozená imunita; Swine; Animals; Salmonella; Immunity, Innate; Toll-Like Receptors; down regulace; prasata; Serogroup; Pattern-recognition receptors; receptory rozpoznávající vzory; Salmonella typhimurium; séroskupina; Salmonella Infections, Animal; T-Lymphocytes; neutrofily; Down-Regulation; Leukocyte; Receptors, Pattern Recognition